Shoulder kinematics of overhead throwing in male professional and semi-professional cricketers - Leondiris, J.; Gray, J.; Dutton, M.; Albertus, Y. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
Throwing in sports is one of the most aggressive and vigorous actions performed by the upper extremity. The purpose of this study was to investigate overhead throwing shoulder kinematics between two different throwing approaches in cricket, throwing from a static versus dynamic position following a run-up. The study sample included twenty (N=20) male professional/semi-professional cricketers. Shoulder kinematic variables were investigated during two different throwing approaches. Dynamic throwing produced significantly greater ball velocity than static throwing. However, shoulder internal rotation velocities at ball release showed no significant differences across static versus dynamic conditions and shoulder kinematics remained largely consistent, except for small variations at MER and MIR in the >75% MTS condition. These findings suggest that the additional ball velocity in dynamic throws was driven by enhanced lower-body force contribution through the momentum of the run rather than altered upper limb mechanics. This highlights the critical role of the lower body in generating throwing velocity while maintaining stable shoulder mechanics. Therefore, this reinforces the importance of full-body coordination in cricket throwing and suggests that training programs should emphasize lower-limb strength and kinetic chain efficiency. Future research should compare elbow kinematics between static and dynamic throwing and investigate shoulder and elbow kinetics during both throw types. The role of neuromuscular activation in optimizing throwing performance and reducing injury risk should also be examined.